ncessant Collapse of Buildings in Nigeria: The Possible Role of the Use of Inappropriate Cement Grade/Strength Class (2014)
The use of low quality concrete has been identified as one of the main causes of the incessant collapse of buildings in Nigeria. Emphasis has been on the use of poor quality aggregates, poor workmanship and the use of lean concrete mix with low cement quantity as the reasons for the low quality of concrete used for building construction in Nigeria. Surveys conducted revealed that in the construction of most privately owned buildings where concrete trial mixes and concrete compressive strength quality assurance tests are not conducted, concretes used for building constructions are produced using the 1:2:4 mix ratio irrespective of the cement grade/strength class. In this paper, the possible role of the use of inappropriate cement grade/strength class as a cause of the incessant collapse of building in Nigeria is investigated. Investigation revealed that the compressive strengths of concrete cubes produced with Portland-limestone cement grade 32.5 using 1:2:4 and 1:1.5:3 mix ratios are less than the 25MPa and 30MPa cube strengths generally recommended for building superstructures and foundations respectively. Conversely, the compressive strengths of concrete cubes produced with Portland-limestone cement grade 42.5 using 1:2:4 and 1:1.5:3 mix ratios exceed the 25MPa and 30MPa generally recommended for building superstructures and foundations respectively. Thus, it can be concluded that the use of inappropriate cement grade (Portland-limestone cement grade 32.5), particularly for the construction of building foundations is a potential cause of the incessant collapse of buildings in Nigeria. It is recommended that the Standards Organisation of Nigeria should embark on creating awareness for Nigerians, particularly, the home owners and the roadside craftsmen that Portland-limestone cement grade 32.5 should not be used for the construction of building load-carrying members, particularly, building foundations in order to reduce the incessant incidence of collapsed building.